2018
DOI: 10.1097/jom.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Impairment From Exposure to Mixed Organic Solvents in Male Shipyard Painters

Abstract: Exposure to organic solvents is associated with obstructive pulmonary dysfunction rather than restrictive pulmonary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, there was a significant moderate negative correlation between FEV1, and FVC with both work experience and cumulative VOC exposure index. Several epidemiological studies have reported similar findings [10,[21][22][23], however, few studies conducted among organized sectors like shipyard and automobile industries have shown no differences in the PFT parameters such as FEV1 and FVC among painters compared to that of the matched unexposed individual [24,25]. A few of the contributing factors that might reduce the pulmonary functions in these unorganized sectors are inadequate health awareness, lack of usage of PPE, and non-adherence to safety measures and protocols by the employees and the employers of these sectors [26].…”
Section: Pulmonary Functions Among Paint Industry Workersmentioning
confidence: 73%
“…Furthermore, there was a significant moderate negative correlation between FEV1, and FVC with both work experience and cumulative VOC exposure index. Several epidemiological studies have reported similar findings [10,[21][22][23], however, few studies conducted among organized sectors like shipyard and automobile industries have shown no differences in the PFT parameters such as FEV1 and FVC among painters compared to that of the matched unexposed individual [24,25]. A few of the contributing factors that might reduce the pulmonary functions in these unorganized sectors are inadequate health awareness, lack of usage of PPE, and non-adherence to safety measures and protocols by the employees and the employers of these sectors [26].…”
Section: Pulmonary Functions Among Paint Industry Workersmentioning
confidence: 73%
“…Exposure to noise in the work environment is perhaps one of the most important reasons for hearing dysfunctions in employees of fabrication industries and others who work with noise producing machines. In case of paint and chemical industries wherein machines such as centrifuges and boilers are common for numerous chemical processes, aromatic chemicals/solvents too play an important role in the deterioration of hearing abilities of such employees [7]. There is adequate proof to prove that a combined effect of exposure to noise as well as solvents cause a higher degree of hearing loss in the employees of solvent industries with constant exposure.…”
Section: Occupational Exposurementioning
confidence: 99%